Use of induction of labour and emergency caesarean section and perinatal outcomes in English maternity services: A national hospital‐level study. (13th June 2022) - Gurol‐Urganci, Ipek; Jardine, Jennifer; Carroll, Fran; Frémeaux, Alissa; Muller, Patrick; Relph, Sophie; Waite, Lara; Webster, Kirstin; Oddie, Sam; Hawdon, Jane; Harris, Tina; Khalil, Asma; et al.
Abstract: Objective: To assess the association between hospital‐level rates of induction of labour and emergency caesarean section, as measures of 'practice style', and rates of adverse perinatal outcomes. Design: National study using electronic maternity records. Setting: English National Health Service. Sample: Hospitals providing maternity care to women between April 2015 and March 2017. Main outcome measures: Stillbirth, admission to a neonatal intensive care unit and babies receiving mechanical ventilation. Results: Among singleton term births, the risk of stillbirth was 0.15%, the risk of admission to a neonatal intensive care unit was 5.4% and the risk of mechanical ventilation 0.54%. There was considerable between‐hospital variation in the rate of induction of labour (minimum 17.5%, maximum 40.7%) and in the rate of emergency caesarean section (minimum 5.6%, maximum 17.1%). Women who gave birth in hospitals with a higher rate of induction of labour had better perinatal outcomes. For each 5%‐point increase in induction, there was a decrease in the risk of term stillbirth of 9% (OR 0.91, 95% CI 0.85–0.97) and a decrease in the risk of mechanical ventilation of 14% (OR 0.86, 95% CI 0.79–0.94). There was no significant association between hospital‐level induction of labour rates and neonatal unit admission at term ( p  > 0.05). There was no significant association between hospital‐level rates of emergency caesarean section and adverse perinatal outcomes (all with p  > 0.05). Conclusions: There is considerable between‐hospital variation in the use of induction of labour and emergency caesarean section. Hospitals with a higher rate of induction had a lower risk of adverse birth outcomes. A similar association was not found for caesarean section. Abstract : Linked article : This article is commented on by Eric Jauniaux, pp. 1907 in this issue. To view this minicommentary visit https://doi.org/10.1111/1471‐0528.17277 This article includes Author Insights, a video abstract available at: https://vimeo.com/bjogabstracts/authorinsights17193